32 Helicopter emergency medical services missions to small islands and the mainland during a 3-year period in denmark. (26th April 2019) - Møller, TP; Ersbøll, AK; Kjærullf, TM; Birmann, K; Knudsen, L; Hansen, TM; Berlac, PA; Lippert, F; Barfod, C
Abstract : Background: The Danish Helicopter Emergency Medical Services (HEMS) is part of the Danish Emergency Medical Services System serving 5.7 million citizens with 1% living on small islands. HEMS is dispatched based on pre-defined criteria including severity and urgency of the case. HEMS is also sent to small islands for less urgent cases, when rapid transport is needed. The study aim was to characterize HEMS missions and the patient population focusing on differences in utilisation between small islands and mainland. Method: Descriptive study of data from the HEMS database in a three-year period from 1 October 2014 to 30 September 2017. All missions in which a patient was either treated on scene or transported by HEMS were included. Results: A total of 6551 HEMS missions were included in the study. Of those 986 (15%) were missions to islands. In total, 92% of missions to islands resulted in patients being transported by HEMS compared to 66% of missions to mainland. Patients from islands were in general older than patients from the mainland. Disease severity, measured with National Advisory Committee for Aeronautics (NACA) score, was lower: 4–7 (serious or life-threatening conditions) in 41% and 66% of missions from islands and mainland, respectively. Conclusion: HEMS missions to islands counts for a substantial part of HEMS activity. The patient population is older and have lower disease severity. More insight into the patient population and outcomes after HEMS transportation would add to the planning and prioritizing of resources. Conflict of interest: None. Funding: The study was partly funded by The Danish HEMS.